Floppy logic : experimenting in the territory between architecture, fashion and textiles - Zilka, Leanne (Actar, 2020)
Floppy Logic is an exploration into the ‘architecture’ of fashion and textiles, and how the concepts, aesthetics, techniques and construction of this architecture might be understood and used to design and fabricate objects and space differently. A key concept here is the Floppy, defined as a quality in material that requires extraneous support to produce architecture. Floppy generally refers to fabric but can also refer to any material that fails when there is not enough support, as is the case with sheet materials when the span between supports exceeds a certain length. Floppy Logic uses a material palette that has been selected for its aesthetic and tactile nature. These materials are typically used superficially and do not have structural qualities to allow them to be applied to the scale of buildings. By exploring form through material play, as fashion designers do with draping fabric over a body, this book expands on approaches to architecture that consider form, structure, skin and enclosure as separate steps.